Pengembangan Modul Ajar Mata Pelajaran IPAS Berbasis Kearifan Lokal Suku Sasak Kelas IV SDN 02 Sembalun Bumbung - M. Guntur Firdaus; Muhammad Tahir; Gozin Najah Rusyada (Mataram University, 2026)
The implementation of the Merdeka Curriculum requires teachers to develop contextual learning resources that accommodate students' characteristics and local potential. However, the teaching modules used in science and social studies (IPAS) learning at SDN 02 Sembalun Bumbung had not integrated the local wisdom of the Sasak ethnic group, resulting in less meaningful learning experiences for students. This study aimed to develop a local wisdom-based IPAS teaching module for fourth-grade students and determine its validity and practicality. This study employed a Research and Development (R&D) approach using the Four-D (4D) development model, consisting of the define, design, develop, and disseminate stages. The research subjects were 27 fourth-grade students of SDN 02 Sembalun Bumbung. Data were collected through interviews and questionnaires, while the research instruments consisted of material expert validation sheets, media expert validation sheets, teacher response questionnaires, and student response questionnaires. The data were analyzed using descriptive qualitative and quantitative techniques. The results indicated that the developed teaching module obtained a validity score of 87.5% from the material expert (valid category) and 91.4% from the media expert (very valid category). Furthermore, the practicality assessment showed a teacher response score of 91.3% and a student response score of 91.1%, both classified as very practical. These findings indicate that the Sasak local wisdom-based IPAS teaching module is valid and practical for use in fourth-grade elementary school learning.